Membrane proteins, detergents and crystals: what is the state of the art?. Issue 12 (1st December 2014) - Loll, Patrick J.
<x xml:space="preserve">Abstract</x> At the time when the first membrane‐protein crystal structure was determined, crystallization of these molecules was widely perceived as extremely arduous. Today, that perception has changed drastically, and the process is regarded as routine (or nearly so). On the occasion of the International Year of Crystallography 2014, this review presents a snapshot of the current state of the art, with an emphasis on the role of detergents in this process. A survey of membrane‐protein crystal structures published since 2012 reveals that the direct crystallization of protein–detergent complexes remains the dominant methodology; in addition, lipidic mesophases have proven immensely useful, particularly in specific niches, and bicelles, while perhaps undervalued, have provided important contributions as well. Evolving trends include the addition of lipids to protein–detergent complexes and the gradual incorporation of new detergents into the standard repertoire. Stability has emerged as a critical parameter controlling how a membrane protein behaves in the presence of detergent, and efforts to enhance stability are discussed. Finally, although discovery‐based screening approaches continue to dwarf mechanistic efforts to unravel crystallization, recent technical advances offer hope that future experiments might incorporate the rational manipulation of crystallization behaviors.